Thermoformed Retainer: An Effective Option for Long-Term Stability. (28th October 2020) - Giancotti, A.; Mozzicato, P.; Mampieri, G.
Abstract : Introduction . The concept of orthodontic retention is moving toward the idea that teeth will move unless retained indefinitely. However, permanent retention implies permanent supervision, and that is where reality clashes with stability. The cornerstone of Essix permanent retention is the complete delegation of responsibility to the patient. Essix retainers have nothing to adjust, but maximum collaboration of the patient is essential to achieve long-term stability. The purpose of this paper is to show the effectiveness of the thermoplastic appliance as a retainer, using a clinical case with a 10-year follow-up. Case Report . A 33-year-old male patient presented with a class II malocclusion division 2 and normal skeletal pattern. According to the patient's desire, a treatment plan was proposed to obtain the aesthetic result of the smile, maintaining the molar and canine class II relationship. The orthodontic therapy was performed by using the Invisalign System. In this case, it was possible to appreciate a posterior occlusal stability after 10 years. Conclusion . Currently, among orthodontists, the use of removable plastic devices is gaining popularity thanks to their capability to encapsulate and retain both posterior and anterior teeth. In this article, the technical features of thermoformed retainers will be described and one clinical case with a 10-year follow-up will be presented to emphasize the effectiveness of these retainers.